Functioning of regulatory "sandboxes": tasks, problems, prospects (Economics and region, 2023)
The article is devoted to the consideration of foreign experience in the regulation of FinTech services. The features of the regulation and supervision system in foreign countries are characterized, the advantages and disadvantages of regulation systems based on rules and principles are determined. A comparative analysis of the use of the regulatory "sandbox" in foreign countries was carried out, common and distinctive features were identified, and the advantages and disadvantages of using this type of regulation of the financial services sector were highlighted. The main Fintech trends in 2023, in particular, embedded finance and BNPL, are identified, and recommendations are provided that would positively affect the successful implementation of the Ukrainian regulatory "sandbox" and contribute to its further modernization in accordance with the world's innovative development of financial technologies. A structural-recommendation model for the creation of domestic regulatory "sandboxes" is proposed.
Keywords: financial markets; regulatory; payment systems; fintech; financial innovations; regtech; supertech